2010
DOI: 10.1089/vim.2009.0086
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Epitopes in the Hemagglutinin of Qinghai-Type Influenza H5N1 Virus

Abstract: The highly pathogenic avian influenza H5N1 viruses have become widespread and evolved into several clades. In our previous studies, the antigenic sites of the H5 hemagglutinin (HA) were characterized by selection and sequencing of escape mutants. In the present studies we analyzed the antigenic epitopes recognized by monoclonal antibodies against avian influenza A/Duck/Novosibirsk/56/05 (H5N1) virus isolated in western Siberia and belonging to subclade 2.2 of the H5N1 viruses. The analysis revealed several ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…A fourth virus (A/Anhui/1/2005) for which limited quantities of reference antigen were available belongs to clade 2·3·4. Although of different clades, these four H5N1 virus HAs demonstrate substantial levels of antigenic homology, sharing more than a half of the antigenic sites discovered by mapping with H5 monoclonal antibodies 27 , 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…A fourth virus (A/Anhui/1/2005) for which limited quantities of reference antigen were available belongs to clade 2·3·4. Although of different clades, these four H5N1 virus HAs demonstrate substantial levels of antigenic homology, sharing more than a half of the antigenic sites discovered by mapping with H5 monoclonal antibodies 27 , 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…During egg passages, immunogenic pressure results in the emergence of progeny viruses with mutations with an altered antigenic pattern (29). In vitro selection in the presence of monoclonal antibodies and polyclonal (rabbitor mouse-derived) antisera was utilized to identify several antigenic epitopes of the hemagglutinin (8,(30)(31)(32)(33) and the neuraminidase (34). Using polyclonal chicken sera in a cell culture system (10), we recently obtained escape variants whose variations reflect immunoescape beyond the major antigenic HA epitopes affecting several viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of antigenic escape was classically investigated by the characterization of escape variants generated in vitro by virus passaging in the presence of monoclonal antibodies (7,8).…”
mentioning
confidence: 99%
“…The importance of two of these residues is stressed by recent studies. Amino acid residues 157 and 178 were identified as relevant in the context of monoclonal immune characterization (37). More importantly, residue 157 was shown to be under positive selection in both avian and human hosts (7).…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, antigenic epitopes in the hemagglutinin (HA) protein were identified by sequencing and structural mapping after generating escape variants in vitro using monoclonal antibodies (21,33,37) or polyclonal (rabbit-or mouse-derived) antiserum (3,23). However, polyclonal antisera from chickens were never used before to generate escape variants, although vaccine escape is a serious problem in influenza virus eradication programs for poultry, especially for HPAIV H5N1 (12).…”
mentioning
confidence: 99%